Development of Novel Anti-Trypanosomal Compounds via Computational, In Vitro and In Vivo Methods - ADLER, NIKOLETTA (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
Human African Trypanosomiasis is a neglected parasitic disease caused by Trypanosoma brucei, which if left untreated eventually leads to coma and death. With no successful vaccine to date, treatment relies on chemotherapy. The currently used 5 parenteral drugs (melarsoprol, pentamidine, suramin, eflornithine, nifurtimox) all have non-negligible toxicity and are complex to use, requiring close monitoring. Additionally, there is emergence of parasite resistance to these drugs, in particular to melarsoprol, the only effective drug for the late, CNS invasive stage of both human infective T. brucei subspecies. Thus, there is a need to develop more tolerable and efficacious treatments. This study investigated the efficacy of various new therapeutic leads as anti-trypanosomal agents, including some repurposed and already FDA-approved. First, a series of vinyl sulfones (40 compounds) from traditional drug discovery pipelines were evaluated for their ability to disrupt the life cycle of trypanosomes in a whole-cell screen of T. b. brucei via a standard Alamar Blue assay. Out of the series tested, 13 compounds were identified with nanomolar activity, making them more potent than the original K777 vinyl sulfone, a promising therapeutic lead against the similar protozoan disease American Trypanosomiais. Additionally, through fluorescence imaging, this study showed that the cysteine protease inhibitor subcellular localisation was in the lysozyme as expected, but surprisingly it was present in nucleus and kinetoplast as well. Further new leads were identified through drug repurposing methods including: a) similarity searches between databases of anti-trypanocidal compounds vs drugs with blood-brain barrier passing capabilities, and b) identifying compounds that modulate the activity of a conserved parasite target, in this case ergosterol, between parasites of similar biology and genomic sequences (T. brucei, T. cruzi, Leishmania). For the first time, the study demonstrated that the antifungals amphotericin B (AmpB) and SPK-843 as well as, fingolimod (FTY720), the first FDA-approved oral agent for the management of relapsing forms of multiple sclerosis, its phosphorylated derivative FTY720P, and endogenous structural mimics sphingosine and sphingosine-1-phosphateare (S1P) were able to kill T. b. brucei in vitro at low and submicromolar concentrations. Specifically, SPK-843, which was tested because of its structural similarity to AmpB, induced parasite death more rapidly and with a greater efficacy than AmpB. The mode of action following AmpB treatment involved membrane permeabilisation as demonstrated by the entry of fluorescent propidium iodide into the cells, possibly via formation of pore-inducing AmpB-ergosterol complexes. Channel formation upon AmpB binding ergosterol was expected as it has been shown in Leishmania and fungal studies. In contrast, there was no membrane disruption detected following SPK-843 treatment. It is proposed here that SPK-843 was able to induce trypansome cell death by simply binding ergosterol, a signaling molecule in BSF rypanosomes, vital to their growth and survival. Interestingly, when the potencies of FTY720, FTY720P, sphingosine and S1P were compared in the different life cycle stages of the parasite all 4 compounds showed higher efficacy against bloodstream form than in procyclic form T. b. brucei. The potency matched those of early stage treatments, suramine and pentamidine. However, FTY720 killed T. brucei faster than FYY720P, with sub-micromolar IC50 occurring after 8 h and 24 h exposure, respectively. Pharmacological time-course studies revealed that FTY720 was irreversible at sub-micromolar concentrations (IC50 ~0.32 μM) and the mode of killing of FTY720 and FTY720P is partly due to membrane disruption and a secondary mechanism of cell division disruption, including failure to undergo cytokinesis, which is apparent from the presence of cells with atypical DNA content observed with fluorescent imaging. Significantly, in trial infections of mice harbouring an acute strain of T. b. brucei, oral administration of fingolimod and intravenous injection of SPK-843 dosed over 5 days was sufficient to clear infection below detectable levels and the lives of the animals were extended by several days. AmpB in its lipid formulation (AmBisome?) did not impede infection. Taken together the results presented in this thesis indicate that lead vinyl sulfones, amphotericin B, SPK-843, and fingolimod present new chemical starting entities for development of anti-trypanosomal agents. The Drugs for Neglected Diseases Initiative (DNDi) highlighted in their Target Product Profile (TPP) that an ideal candidate would have the potential to be used as a treatment for both stages of the disease. Importantly, fingolimod is known to readily penetrate the CNS and may provide the most promise for future treatment of both haemolymphatic and meningoencephalitic stages of trypanosomiasis. For future work, it would be essential to undertake further in vivo experiments using a chronic model of trypanosomiais with longer treatment periods to improve fingolimod efficacy in an animal model and to clear infection completely. Also, further pharmacodynamics investigations of vinyl sulfones and in vitro studies investigating the potential to increase efficacy of SPK-843 and ampothericin B when used in combination with current HAT drugs are warranted.
APPROVED
Keywords: anti-trypnosomal, cysteine protease inhibitor, drug repurposing, Fingolimod, S1P, SPK-843, Amphotericin B